Relationship between systolic hypertension assessed by 24‐hour ambulatory blood pressure monitoring and aortic diameters in young women with Turner syndrome. (30th April 2019) - Lee, Yun Jeong; Kim, Shin Mi; Lee, Young Ah; Kim, Gi Beom; Shin, Choong Ho; Yang, Sei Won
Abstract: Objective: Patients with Turner syndrome (TS) are at high risk for cardiovascular morbidity and mortality due to aortic dilation. We evaluated the prevalence of hypertension and its risk factors and investigated the relationship between systolic hypertension and aortic diameter in young patients with TS. Design: Observational, cross‐sectional study. Patients and measurements: Forty‐two patients with TS (15‐35 years) who had achieved final adult heights underwent 24‐h ambulatory blood pressure monitoring (ABPM). Fasting glucose, insulin and lipid profiles were measured. The homeostasis model assessment of insulin resistance (HOMA‐IR) was calculated. Echocardiography was performed to evaluate aortic diameters (aortic annulus, aortic root at the sinuses of Valsalva, sinotubular junction and ascending aorta), which were converted into Turner‐specific z ‐scores. Results: Systolic and/or diastolic hypertension was identified in 71.4% (n = 30) of patients, as assessed by 24‐hour ABPM. Twenty‐eight patients (66.7%) were nondippers. Patients with systolic hypertension (n = 8, 19.0%) had a higher weight, waist circumference and HOMA‐IR levels than those without hypertension ( P < 0.05 for all). After adjusting for covariates, HOMA‐IR was independently associated with systolic hypertension (odds ratio 10.1, P = 0.043). After adjusting for age and bicuspid aortic valve, systolic hypertension was independently related to increased aortic diameter at the aortic annulus (β = 1.064, P = 0.009) and sinotubular junction (β = 1.124, P = 0.016). Conclusions: Hypertension is highly prevalent and independently associated with IR in young patients with TS. The significant relationship between systolic hypertension and aortic diameters underscores the importance of BP and IR control.